The Transnationalism of Democracy and Power Multiplicity in Indonesia: A Critical Perspective - Ade Marup Wirasenjaya; Purwo Santoso (Universitas Muhammadiyah Yogyakarta, 2024)
This article explores the concepts of power and democracy within the context of transnationalism, with a specific focus on Indonesia. It traces the foundational ideas of power from classical political thought to contemporary notions, bridging an understanding that reflects the complexity and multiplicity of power in a transnational world. The author emphasizes the importance of recognizing power multiplicity as a new way to perceive power, given the current historical structure that has produced various actors, transformed institutions, and deconstructed political arenas from traditional models to contemporary ones. The transnational historical structure not only creates new arenas for power but also shapes new methods of power production. These innovations have profound implications for political life and the current face of democracy in Indonesia, reflecting a transition from old paradigms to modern interpretations. The research offers a critical perspective on how transnational influences interact with domestic structure to redefine democracy and power dynamic in a rapidly globalizing world.